Yield and Accumulation Trend of Biomass and L‐DOPA in Different Parts of Eight Faba Bean Cultivars. Issue 5 (5th July 2018) - Etemadi, F.; Hashemi, M.; Autio, Wesley R.; Mangan, Francis X.; Zandvakili, OmidReza
Abstract : Faba bean ( Vicia faba L.) is a rich source of 3, 4‐dihydroxyphenyl‐L‐alanine (L‐DOPA) and thus can be used as an alternative to synthetic compounds for curing Parkinson's disease. Accumulation of biomass and L‐DOPA in different organs of eight cultivars of faba bean was investigated in a field‐grown study in 2015 and 2016 at the Research and Education Center, University of Massachusetts, Amherst. Plants were harvested at five stages of growth and partitioned into various organs including roots, leaves, stems, pod walls, and fresh seeds. 'Aquadulce' and 'Delle Cascine' outyielded other cultivars in both years. Averaged over 2 yr, Aquadulce and Delle Cascine produced 16, 152 and 16, 270 kg fresh pods ha −1 . Thus, the highest L‐DOPA seed yield was obtained from these two cultivars. Accumulation of L‐DOPA during faba bean growing period exhibited a quadratic trend and reached its peak values at 65 to 75 d after transplanting, whereas accumulation of dry matter exhibited a linear trend. The results revealed that distribution of dry matter among various organs of faba bean was significantly different among the cultivars. The L‐DOPA yield (concentration × dry matter) varied dramatically among the cultivars where Aquadulce and 'Sweet Lorane' yielded 55.2 and 6.4 kg L‐DOPA ha −1, respectively. The superiority of Aquadulce in regard to the L‐DOPA yield was primarily due to its photosynthesis capacity, which produced 6871 kg dry matter ha −1, rather than its L‐DOPA concentration. We concluded that if the goal of producing faba bean is dual purpose, the leaves can be used as the richest L‐DOPA organ, whereas the green pods can be harvested as a cash crop.